ANALYSIS OF RE 643.978 (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
There has been a growing evolution of judicial protection, the process, which until then was eminently individualistic, began to understand social and transindividual repercussions resulting from its results. Such repercussions were necessary for the absorption of the new emerging reality: the protection of the collectivity. This undoubtedly benefits the judiciary, either by guaranteeing access to justice or by the economy and procedural speed. However, despite the gradual evolution, the collective protection still finds certain obstacles to its effectiveness, among them, the sole paragraph of the first article of Law no. verse about FGTS, finding confrontation in the Federal Constitution, notably in article 129, item III.Keywords: Public civil action; FGTS; Public Ministry; Federal Constitution.